Anti-inflammatory and toxicity studies of atranorin extracted from Cladina kalbii Ahti in rodents - Melo, Marcelia Garcez Dória de (2011)
Atranorin (ATR) is the main compound from the lichen Cladina kalbii Ahti, which grows in the arid regions of northeastern Brazil. This study was conducted to evaluate the anti-inflammatory and toxicological properties of ATR. To evaluate anti-inflammatory properties, paw edema was induced by injecting 0.1 mL of carrageenan into the subplantar region of the right hind paw of rats, and leukocyte migration was induced by injection of 500 µL of carrageenan into the peritoneal cavity of mice. In addition, we determined ATR cytotoxicity in L929 cells by MTT assay and acute (5 g/kg-single dose) and subchronic (50 mg/kg-30 days) toxicity tests in Wistar rats. The results showed that ATR (100 mg/kg and 200 mg/kg) exhibited significant anti-inflammatory activity (paw edema and leukocyte migration). In the acute toxicity test, the animals showed hypoactivity and lethargy during the initial period (first 6 hours) and increase in total protein, total and indirect bilirubin, and alkaline phosphatase after 14 days in ATR-treated male rats. The subchronic toxicity test revealed increases in total protein, globulin, gamma-glutamyl transferase, alkaline phosphatase, and total and direct bilirubin in ATR-treated female rats. Histological analysis revealed no changes in the architecture and morphology of the organs. These results suggest that ATR has significant anti-inflammatory activity, with no significant acute and subchronic toxicity or cytotoxicity._________________________________________________________________________________________ RESUMO: Atranorina (ATR) é o principal composto do líquen Cladina kalbii Ahti, que cresce em terras áridas do nordeste brasileiro. Este estudo foi realizado para avaliar as propriedades antiinflamatórias e toxicológicas da ATR. Para avaliar as propriedades antiinflamatórias, o edema de pata foi induzido, administrando-se 0,1 mL de carragenina na região subplantar da pata traseira direita e a migração leucocitária foi induzida pela injeção de 500 µL de carragenina no peritônio. Além disso, determinou-se a citotoxicidade da ATR, utilizando-se a linhagem celular L929, através do teste de MTT e dos testes de toxicidade aguda (5 g/kg - dose única) e subcrônica (50 mg/kg-30 dias) em ratos Wistar. Os resultados mostraram que nas doses de (100 mg/kg e 200 mg/kg) a ATR exibiu atividade antiinflamatória significativa nos ensaios de edema de pata e migração leucocitária. Nos testes de toxicidade aguda, os animais apresentaram hipoatividade e letargia no período inicial (primeiras 6 horas) e aumento das proteínas totais, bilirrubinas total e indireta e fosfatase alcalina depois de 14 dias nos machos tratados. Para o ensaio subcrônico, houve aumento das proteínas totais, gama-glutamil-transferase, fosfatase alcalina e bilirrubina total e direta nas fêmeas tratadas com ATR. Não foram encontradas alterações na arquitetura e morfologia das lâminas histológicas observadas. Esses resultados sugerem que a ATR apresenta atividade antiinflamatória significativa, sem apresentar significativa toxicidade aguda, subcrônica e citotoxicidade.